Responsible Tourism and Landscape as an Alternative for the Development of Depopulated Rural Areas: Reflections and teaching proposals for the Genal valley territory from the School of Architecture, University of Malaga - Asencio-Juncal, Jorge; Nebot-Gómez de Salazar, Nuria; Marín-Malavé, Juan Antonio; Chamizo-Nieto, Francisco José (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The process of rural depopulation in the Genal Valley, in southern Spain, has been aggravated in recent decades, caused by the exodus of inhabitants in search of job opportunities or better services. The physical proximity of Costa del Sol area, in constant tourist growth since 1960s, has been a strong attraction for the active population, and it has favoured this dynamic. The Genal valley and its interrelation with Costa del Sol area is of great interest and it has been proposed as a study laboratory within the subject “Heritage, Tourism and Territory” in the School of Architecture of Malaga.